Effect of structural parameters on the tensile properties of multilayer 3D composites from Tururi palm tree (Manicaria saccifera Gaertn) fibrous material. (15th February 2017) - Seyam, Abdel-Fattah M.; Monteiro, Amanda Sousa; Midani, Mohamad; Baruque-Ramos, Julia
Abstract: Tururi ( Manicaria saccifera Gaertn.) is a naturally integrated fibrous structure in a form of sac, which protects the fruits of the Amazon Ubuçu palm tree. The goal of this research was to develop and characterize multilayer 3D green composites from Tururi fibrous material and identify applications based on their performance. A total of 12 composite samples were fabricated using Vacuum Assisted Resin Transfer Molding Technique (VARTM) to study the effect of the structural parameters, namely, number of Tururi fibrous layers, fiber orientation, and fiber volume fraction on the tensile and impact behavior of the final composites. The focus of this paper will be on the tensile properties in the sac and cross directions, as for the impact properties, it will be covered in another publication. It was found that a proper stacking sequence, can produce composites from Tururi fibers with quasi-isotropic tensile behavior, and with the proper combination of number of layers, and stretch %, the tensile properties of the produced composite can be optimized.